LEGAL PROTECTION FOR CUSTOMERS AGAINST PENALTY EXEMPTION CLAUSES IN STANDARD AGREEMENTS DURING THE COVID-19 PANDEMIC IN INDONESIA - Bahmid, Bahmid; Marqom, Ruzian; Siregar, Siti Hajar; Basuni, Zakiyah An Nisa’; Andalarl, Fahrul Azmi (Citra Justicia : Majalah Hukum dan Dinamika Masyarakat, 2024)
This research is a theoretical study of the early repayment clause in standard banking credit agreements during the pandemic. The issue at hand is how standard agreements containing force majeure clauses are examined in light of theories of justice and the doctrine of abuse of circumstances during the COVID-19 pandemic. The research method used in this study is juridical-normative, with a legislative approach. In standard agreements, debtors are only given limited freedom to negotiate, which is associated with consumer protection. Creditors face potential gains and losses due to early repayments, while debtors are constantly at risk of suffering losses, thus undermining fairness. Therefore, the government must intervene to protect society by establishing regulations that can rectify imbalances in banking credit agreements.Keywords: Protection, Agreement, Clause, Creditor, Debtor, BankLEGAL PROTECTION FOR CUSTOMERS AGAINST PENALTY EXEMPTION CLAUSES IN STANDARD AGREEMENTS DURING THE COVID-19 PANDEMIC IN INDONESIA